e-Lingua 1/2025 / Norhaslinda Hassan ... [et al.] - Hassan, Norhaslinda; Razali, Wan Noorli; Zulkifli, Che Nooryohana; Ahmad Zubir, Hanani; Mohd Amin, Noraziah; Mohamad Fadzil, Fasyin Diyana; Abdul Halil, Norhafizah; Kudus, Nazima Versay; Lim, Teck Heng; Seng, Hui Zanne (Academy of Language Studies, 2025)
From the Editorial Team *3 Department News & Reports *4 Club News & Report *27 Self-Love First *39 Travelling *46 Home Garden *58 Teaching & Learning *64 Lecturer's Contribution *68 Creative Writing *81 The Team *90